Abdominal Tuberculosis: Diagnostic and Management Problems - Noto Dwimartutie; Iskandar A; Marcellus Simadibrata; Ari F Syam; Ceva W Pitoyo; Andri Sulaiman; Tony Loho (The Indonesian Society for Digestive Endoscopy, 2006)
Abdominal tuberculosis, as one of the manifestations of extrapulmonary tuberculosis, may involve gastrointestinal tract, peritoneum, mesenteric lymph nodes, liver, and also spleen. Most patients have constitutional symptoms of fever, pain, diarrhea, constipation, alternating constipation and diarrhea, weight loss, anorexia and malaise. It also has an insidious course without any specific laboratory, radiological or clinical findings and makes it difficult to diagnosis. Anti tuberculosis treatments with initiation phase for 2 months and continue with continuation phase for 7 months is effective. Steroids may be used to reduce acute inflammation and limit delayed fibrotic complications. We report a male patient with abdominal tuberculosis involving peritoneum, liver, colon, paraaorta lymph nodes, and spleen, which at first suggested as a malignancy. Drug induced hepatitis due to anti tuberculosis drug during treatment was emerged and substituted with other regimen. After given anti tuberculosis treatment and steroid as adjunctive treatment, the clinical condition of patient was improved. Keywords: abdominal tuberculosis, anti tuberculosis treatment, drug induced hepatitis